2019
DOI: 10.21315/tlsr2019.30.3.1
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Primer-Specific Targeting on Mitochondrial Cytochrome b Combined with Real-Time Polymerase Chain Reaction for the Analysis of Dog Meat in Meatballs

Abstract: Highlights • Cyt-55 primer has been designed for real-time polymerase chain reaction for detection of dog meat in meatballs. • Cyt b-55 could specifically amplify DNA from dog meat using an optimum annealing temperature of 57.9°C. • Real-time PCR using Cyt b-55 primer could be proposed as a standard method for the identification of dog meat in food products for halal authentication study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Therefore, it could be stated that the LoD value of real-time PCR for analysis of dog DNA was 5 pg. Manalu et al [26] reported that Real-PCR using primers targeting on Cyt-b gene primer could detect the presence of DNA at a concentration as low as 0.25 ng/mL, corresponding to 1% of dog meat in beef meatballs. Rahman et al [4] reported LoD values of 0.02 ng dog DNA corresponding to 0.1% of dog meat in meatball samples, and this LoD value was similar to that reported by Ali et al [25] in frankfurters using chicken and beef meat.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it could be stated that the LoD value of real-time PCR for analysis of dog DNA was 5 pg. Manalu et al [26] reported that Real-PCR using primers targeting on Cyt-b gene primer could detect the presence of DNA at a concentration as low as 0.25 ng/mL, corresponding to 1% of dog meat in beef meatballs. Rahman et al [4] reported LoD values of 0.02 ng dog DNA corresponding to 0.1% of dog meat in meatball samples, and this LoD value was similar to that reported by Ali et al [25] in frankfurters using chicken and beef meat.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Rahman et al [4] have used primers targeting the cytochrome b gene (Cyt-b) in meatball samples. Primers targeting on Cyt-b gene were used for the analysis of DNA dog meat in commercial frankfurters [25] and in meatball samples [26]. However, the application of PCR using primers targeting mitochondrial cytochrome c oxidase subunit 1 (COI) was limited.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition, many molecular-based analysis methods can be used because of the fast process and results in research, one of which is the DNA-based method which has been widely developed, such as fingerprinting using PCR, multiplex PCR assay, and real-time PCR; this method has been widely used for several last decades ( Manalu and Rohman, 2019 ). The results of DNA amplification of the chuA gene of the invasive enterohemorrhagic species E. coli 0157:H7 using qPCR can be used as an analysis to detect the presence of DNA other than in horse feces.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has used a variety of primer sources of DNA extracted from meat samples. The species-specific primers (SSPs) focusing on Mitochondrial Cytochrome b have been applied in the studies for the identification of CMballs [ 24 ], dog meatballs [ 4 ], and wild boar meatballs [ 25 , 26 ], respectively. The use of SSP that targets D-loop mitochondria for authentication of wild boar in meatballs was done by Arini et al [ 25 ].…”
Section: Introductionmentioning
confidence: 99%